Decomposing patterns of emission intensity in the EU and China: How much does trade matter? - Valeria di Cosmo; Marie Hyland (The Economic and Social Research Institute (ESRI), 2013)
This paper uses data from the World Input Output Database (WIOD) to examine channels through which CO2 emissions are embodied within and imported into the European production process. We apply a metric to calculate sectoral emission intensity and thus rank countries and sectors in the EU in terms of their emission intensity, and look at the evolution of patterns of emission intensity in 2005 and in 2009. We use an input-output price model to simulate the effect that a rise in the price of EU-ETS allowances, from 17 to 25 /tonne, would have on the final price of goods in each EU country and sector. We find that all countries in the EU reduced the emission-intensity of their production processes from 2005 to 2009, and we find that the reduction was greatest in those sectors regulated under the ETS. Comparisons of emission intensity between countries show that industries in Central and Eastern Europe are more emission intensive than those of Northern Europe, where industries import emission-intensive goods rather than producing them domestically. Finally we examine the trade in intermediate goods from China into the EU to examine possible increases in carbon leakage from 2005 to 2009. Results show that while emissions embodied in imported intermediate goods have increased from 2005 to 2009, this increase is not limited to, nor particularly notable in, the sectors regulated by the ETS.
Keywords: 330; energy demand; Greenhouse gas emissions; Input-output; price analysis